PWE-003 Ileostomy Formation as A Result of Surgical Management for Crohn's Disease: A Qualitative Study. (17th August 2016) - Morris, A; Leach, B
Abstract : Introduction: Ileostomy formation for severe Crohn's Disease (CD) brings physical and psychosocial sequelae requiring people to self-manage numerous lifestyle changes. However pre and post formation experiences of an ileostomy and adaptation are underexplored. This qualitative study explores the experiences of adults with CD pre and post ileostomy formation. Methods: A phenomenological design utilised in-depth semi-structured interviews with adults with Crohn's and ileostomy. Convenience sample recruitment via Coventry Iileostomy and Internal Pouch Support Group was employed. A topic guide covered the areas of life before and after an ileostomy and feelings about the support received. Interviews were recorded and transcribed verbatim. Data was explored and findings interpreted using Framework Analysis. NVIVO software was used for data management. Member checking and internal peer review were undertaken. Participants gave written informed consent. Results: Ten adults (4 men 6 women) with a mean age of 52.2 (±19) years had a mean experience of 18.8(±11.4) years of living with an ileostomy. Three major themes emerged: (1) Controlling nature of Crohn's embodied by pain, diarrhoea, vomiting, and low mood as a life "not worth living" (2) New life post stoma formation facilitated "total freedom" and re-engagement with work/socialising (as a result, individuals "refused to have the ileostomy reversed") (3) Peer support along with clinical nutrition updates would have helped as "people doing it themselves understand". One minor theme emerged around a new life: (2 a) memories of CD affected life with an ileostomy. These experiences meant that certain health promoting behaviours, for example, intentional weight loss for corticosteroid/ smoking cessation induced weight gain, were avoided as individuals were "not going back to a walking skeleton" pre stoma formation. Conclusion: Life with Crohn's was debilitating before an ileostomy. Individuals viewed ileostomy construction as a positive experience as the stoma helped manage the CD symptoms. Memories of life pre-ileostomy may affect individuals' behaviour post-ileostomy formation. Implications for clinical practice include multi-disciplinary team (MDT) members understanding that memories of CD may still affect health related behaviour post stoma formation which may require further MDT support. Disclosure of Interest: None Declared